The gut commensal bacterium Enterococcus faecalis LX10 contributes to defending against Nosema bombycis infection in Bombyx mori. Issue 6 (16th March 2022) - Zhang, Xiancui; Feng, Huihui; He, Jintao; Liang, Xili; Zhang, Nan; Shao, Yongqi; Zhang, Fan; Lu, Xingmeng
Abstract: BACKGROUND: Microsporidia, a group of obligate intracellular fungal‐related parasites, have been used as efficient biocontrol agents for agriculture and forestry pests due to their host specificity and transovarial transmission. They mainly infect insect pests through the intestinal tract, but the interactions between microsporidia and the gut microbiota of the host have not been well demonstrated. RESULTS: Based on the microsporidia– Bombyx mori model, we report that the susceptibility of silkworms to exposure to the microsporidium Nosema bombycis was both dose and time dependent. Comparative analyses of the silkworm gut microbiome revealed substantially increased abundance of Enterococcus belonging to Firmicutes after N. bombycis infection. Furthermore, a bacterial strain (LX10) was obtained from the gut of B. mori and identified as Enterococcus faecalis based on 16S rRNA sequence analysis. E. faecalis LX10 reduced the N. bombycis spore germination rate and the infection efficiency in vitro and in vivo, as confirmed by bioassay tests and histopathological analyses. In addition, after simultaneous oral feeding with E. faecalis LX10 and N. bombycis, gene (Akirin, Cecropin A, Mesh, Ssk, DUOX and NOS) expression, hydrogen peroxide and nitric oxide levels, and glutathione S‐transferase (GST) activity showed different degrees of recovery and correction compared with those under N. bombycis infection alone. Finally, the enterococcin LX protein was identified from sterile LX10 fermentation liquid based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) analysis. CONCLUSION: Altogether, the results revealed that E. faecalis LX10 with anti‐ N. bombycis activity might play an important role in protecting silkworms from microsporidia. Removal of these specific commensal bacteria with antibiotics and utilization of transgenic symbiotic systems may effectively improve the biocontrol value of microsporidia. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : According to the microsporidia– Bombyx mori model, we revealed that Enterococcus with anti‐ Nosema bombycis activity might play an important role in protecting silkworms from microsporidia. The present study provides a clear profile of the complex interplay among microsporidia, silkworms, and gut microbiome.